Rare earth doped alkali metal chloride composite ceramic and cold sintering preparation method thereof
The preparation of rare earth doped alkali metal chloride composite ceramics under low temperature conditions through cold sintering method, solving the problems of high temperature and low energy efficiency in traditional ceramic sintering processes, achieving high stability and high luminous efficiency of ceramics, and is suitable for the field of new generation information technology.
Patent Information
- Application Number
- CN202510294240.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-13
AI Technical Summary
The sintering and preparation process of traditional ceramic materials has problems such as high temperature, low energy efficiency, phase decomposition and diffusion, and the uneven distribution of rare earth doping affects the performance of ceramics.
The cold sintering method is used to prepare rare earth doped alkali metal chloride composite ceramics under low temperature (<300℃). The high stability and high luminous efficiency of the ceramics are achieved through raw material purification, process optimization and ultrasonic-assisted hot press sintering.
It realizes low energy consumption and low cost preparation of ceramic materials, improves the density, mechanical properties and luminous efficiency of ceramics, and is suitable for electronics, lighting, flat panel display and laser fields.
Smart Images

Figure CN119797919A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic non-metallic materials and luminescent ceramics, and specifically relates to a rare earth doped alkali metal chloride composite ceramic and a cold sintering preparation method thereof. Background Art
[0002] The traditional sintering preparation process of ceramic materials has problems such as high temperature, low energy efficiency, phase decomposition and diffusion. Existing sintering technologies, such as microwave sintering, spark plasma sintering, and rapid sintering, can reduce the sintering temperature of ceramic materials. However, the sintering temperature of these processes is still too high for some special ceramic materials. Therefore, there is an urgent need for a low-energy, low-cost sintering process while ensuring the density and stability of the ceramic structure. Traditional ceramic sintering needs to be carried out at high temperature (>1000℃), which leads to grain coarsening, high energy consumption, and uneven distribution of rare earth doping. Cold sintering is a process that uses transient liquid phase and uniaxial pressure at low temperature (<300℃) or even room temperature to densify various inorganic materials, especially ceramic materials that are unstable at high temperature, and can also improve the mechanical properties and durability of ceramic materials. Therefore, cold sintering technology has attracted much attention since its birth. Alkali metal chlorides have the advantages of simple structure, low cost and wide band gap. They are good raw materials for preparing ceramics and are easy to achieve ion doping. Pure and ion-doped alkali metal halide ceramics have broad application prospects in the fields of electricity, optics, detection, etc. Lei Li et al. prepared NaCl and LiF ceramics by cold sintering and studied the influence of water content on electrical and mechanical properties. Yongtao Li et al. prepared NaCl:Eu ceramics by cold sintering and analyzed their structure and properties. However, there are few reports on the preparation process and performance research of rare earth-doped alkali metal composite halide ceramics.
[0003] Alkali metal chloride composite ceramics have a large lattice energy, which can provide more coordination space for Eu, making it easier for Eu ions to maintain a stable luminescent state in the composite ceramics, and not prone to self-excitation effect or light damage. Especially under low-temperature sintering conditions, the lattice structure can be better maintained. Compared with NaCl:Eu ceramics, the lattice is more stable and not prone to lattice distortion. The solubility of composite ceramics is higher. Therefore, during the cold sintering process, the distribution of Eu ions in the lattice is more uniform, which can avoid the uneven doping or ion aggregation phenomenon that occurs in the traditional sintering process. In addition, due to its large lattice constant and lower thermal expansion coefficient, alkali metal halide composite ceramics are more stable than traditional ceramics in high temperature changes or extreme temperature environments in environments with large temperature fluctuations, and are suitable for optical components or other high-temperature applications in high-temperature working environments. However, the raw material purification, process optimization and luminous efficiency improvement of rare earth-doped alkali metal halide composite ceramics need further research. Therefore, in view of the shortcomings of the prior art, the present invention provides a rare earth-doped alkali metal chloride composite ceramic and a cold sintering preparation method thereof, and successfully prepares a high-performance rare earth-doped alkali metal halide composite ceramic through raw material purification, process optimization, etc., which effectively solves the problems of low raw material purity, low luminous efficiency, and complex preparation process, and promotes the widespread application of ceramics in new generation information technology fields such as electronics, lighting, flat panel displays and lasers. Summary of the invention
[0004] The purpose of the present invention is to provide a rare earth doped alkali metal chloride composite ceramic and a cold sintering preparation method thereof, which has low equipment cost, low preparation energy consumption, simple preparation process, and the prepared ceramic material has high stability and high luminous efficiency.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a rare earth doped alkali metal chloride composite ceramic and a cold sintering preparation method thereof, comprising the following steps:
[0007] (1) Raw material purification: KOH, NaOH and NH4Cl with a purity of 99.7% were added to HCl solution, and the mixed solution was concentrated and evaporated at 60℃~100℃ to obtain a solid mixture. The solid mixture was placed in a quartz container and vacuum dehydrated at 230℃~260℃ to obtain a dehydrated product. The product was then calcined at 420℃~480℃ in an inert atmosphere to obtain K with a purity of 99.9%. x Na 1-x Cl (0.1≤x≤0.9) raw material;
[0008] (2) K with a purity of 99.9% x Na1-x Cl and EuCl3 are weighed in stoichiometric ratio. x Na 1-x The molar ratio of Cl to EuCl3 is 0.5:(0.002 - 0.02), and an organic flux accounting for 0.1 - 1% of the total mass of the raw materials is added;
[0009] (3) Add the weighed raw material in step (2) into deionized water (resistivity not less than 18 MΩ·cm), stir and completely dissolve, the mass ratio of raw material to deionized water is 1:(3 - 5), dry at 60 - 100 °C for 15 - 25 h, grind for 10 - 20 min, and then put into a grinding tool;
[0010] (4) The mixture in the mold of step (3) is subjected to uniaxial hot pressing sintering, while applying ultrasonic assistance with a frequency of 20-40 kHz and a power of 100-500 W, the uniaxial pressure is 50-400 MPa, the pressure application and pressure release rate is 5-10 MPa / min, the sintering temperature is 100-225°C, the sintering time is 20-30 min, the sintering heating and cooling rate is 8-15°C / min, and after sintering, the power is turned off, the pressure is released, the mixture is cooled, and the ceramic sheet is obtained after demolding and drying.
[0011] Furthermore, in step (2), the organic flux is polyethylene glycol (PEG).
[0012] Furthermore, in step (4), the application time of the ultrasonic wave is 50-80% of the entire sintering process.
[0013] The beneficial effects of the present invention are as follows:
[0014] The present invention synthesizes K by cold sintering under variable temperature and pressure conditions. x Na 1-x Cl:Eu ceramics. The obtained ceramic test shows that with the increase of Eu concentration, the emission spectrum intensity increases, and the luminescence performance is optimal when the doping concentration is 0.008 mol%, the sintering temperature is 125 ° C, and the pressure is 300 MPa. In addition, the raw material preparation process in the present invention is simple, which can reduce the production cost, is suitable for large-scale industrial production, and has broad application prospects in the fields of lighting, flat panel display, laser and bioluminescent labeling. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the XRD of the KNaCl:Eu ceramic of the present invention sintered at 125°C.
[0017] Figure 2The XPS spectra of the KNaCl:Eu ceramic of the present invention are shown in Figure 1. (a) is the XPS of KNaCl:0.008Eu, and (b) is the XPS of K2p 3 / 2 and K 2p 1 / 2 XPS fitting peaks, (c) are Cl 2p 3 / 2 (d) is the XPS fitting peak of Na 1s, (e) is the XPS fitting peak of Eu3d 5 / 2 and Eu 3d 3 / 2 XPS fitting peaks.
[0018] Figure 3 : It is the SEM image of the fracture of KNaCl:Eu ceramic of the present invention, (a)-(c) in the figure are SEM images and tomography of KNaCl:0.008Eu ceramic samples, (d) is the SEM image of KNaCl:0.008Eu at a sintering temperature of 225°C, (e) is the SEM image of KNaCl:0.008Eu ceramic under uniaxial pressure of 50MPa, (f) is the SEM image of KNaCl:0.008Eu ceramic under uniaxial pressure of 100MPa, (g) is the SEM image of KNaCl:0.008Eu ceramic under uniaxial pressure of 200MPa, and (h) is the SEM image of KNaCl:0.008Eu ceramic under uniaxial pressure of 300MPa.
[0019] Figure 4 It is the fluorescence spectrum of the KNaCl:Eu ceramic of the present invention, Figure (a) is the excitation spectrum of KNaCl:Eu at 613 nm, Figure (b) is the emission spectrum of KNaCl:Eu at 391 nm, and (c) is the emission spectrum of KNaCl:0.008Eu at different sintering temperatures.
[0020] Figure 5 It is the TG curve of the KNaCl:Eu ceramic of the present invention.
[0021] Figure 6 (a) is KNaCl:0.008Eu ceramic sheet, Figure 6 (b) KNaCl:0.008Eu ceramic sheet under ultraviolet light excitation. DETAILED DESCRIPTION
[0023] The specific implementation of the present invention will be further described below in conjunction with the accompanying drawings:
[0024] Embodiment 1: A rare earth doped alkali metal chloride composite ceramic and a cold sintering preparation method thereof, specifically comprising the following steps:
[0025] (1) KOH, NaOH and NH4Cl with a purity of 99.7% were added to HCl solution, concentrated and evaporated at 80°C to obtain a solid mixture, the solid mixture was placed in a quartz container and vacuum dehydrated at 250°C for 2 h, and then the product was calcined at 450°C in an inert atmosphere to obtain K with a purity of 99.9%. 0.5 Na 0.5 Cl raw material;
[0026] (2) K with a purity of 99.9% 0.5 Na 0.5 Cl and EuCl3 were weighed in a stoichiometric ratio of 1:(0.002-0.02), and polyethylene glycol (PEG) accounting for 0.4% of the total weight of the raw materials was added;
[0027] (3) Add the weighed raw materials in step (2) into deionized water, stir and completely dissolve them, dry them at 80°C for 24 hours, grind the dried mixture for 20 minutes, and then put it into a grinding tool;
[0028] (4) pressing the mixture in the mold of step (3) into a tablet using a tablet press and uniaxial hot pressing sintering, while applying ultrasonic assistance with a frequency of 30 kHz and a power of 300 W;
[0029] (5) The uniaxial pressure in step (4) is 300 MPa, the temperature is controlled by an external heating coil and a temperature controller, the sintering temperature is 125 °C, the sintering time is 30 min, and the sintering heating and cooling rates are 10 °C / min;
[0030] (6) After sintering, the power is turned off, the pressure is released, the sample is cooled, demolded and dried to obtain a ceramic sheet. The fluorescence intensity of the sample increases with the increase of the doping concentration, and the luminescence intensity is optimal when the doping concentration is 0.008 mol%.
[0031] Embodiment 2: A rare earth doped alkali metal chloride composite ceramic and a cold sintering preparation method thereof, specifically comprising the following steps:
[0032] (1) KOH, NaOH and NH4Cl with a purity of 99.7% were added to HCl solution, concentrated and evaporated at 80°C to obtain a solid mixture, the solid mixture was placed in a quartz container and vacuum dehydrated at 250°C for 2 h, and then the product was calcined at 450°C in an inert atmosphere to obtain K with a purity of 99.9%. 0.5 Na 0.5 Cl raw material;
[0033] (2) K with a purity of 99.9% 0.5 Na 0.5Cl and EuCl3 were weighed in a stoichiometric ratio of 1:0.008, and polyethylene glycol (PEG) accounting for 0.4% of the total weight of the raw materials was added;
[0034] (3) Add the weighed raw materials in step (2) into deionized water, stir and completely dissolve them, dry them at 80°C for 24 hours, grind the dried mixture for 20 minutes, and then put it into a grinding tool;
[0035] (4) pressing the mixture in the mold of step (3) into a tablet using a tablet press and uniaxial hot pressing sintering, while applying ultrasonic assistance with a frequency of 30 kHz and a power of 300 W;
[0036] (5) In step (4), the uniaxial pressure is 300 MPa, and the temperature is controlled by an external heating coil and a temperature controller, and is heated from room temperature to 100 °C, 125 °C, 150 °C, 175 °C, 200 °C, and 225 °C, respectively. The sintering time is 30 min, and the sintering heating and cooling rates are 10 °C / min.
[0037] (6) After sintering, the power is turned off, the pressure is released, the sample is cooled, demolded and dried to obtain a ceramic sheet. The fluorescence intensity of the sample increases with the increase of sintering temperature, and the best luminescence intensity is achieved at 125 °C.
[0038] Embodiment 3: A rare earth doped alkali metal chloride composite ceramic and a cold sintering preparation method thereof, specifically comprising the following steps:
[0039] (1) KOH, NaOH and NH4Cl with a purity of 99.7% were added to HCl solution, concentrated and evaporated at 80°C to obtain a solid mixture, the solid mixture was placed in a quartz container and vacuum dehydrated at 250°C for 2 h, and then the product was calcined at 450°C in an inert atmosphere to obtain K with a purity of 99.9%. 0.5 Na 0.5 Cl raw material;
[0040] (2) K with a purity of 99.9% 0.5 Na 0.5 Cl and EuCl3 were weighed in a stoichiometric ratio of 1:0.008, and polyethylene glycol (PEG) accounting for 0.4% of the total weight of the raw materials was added;
[0041] (3) Add the weighed raw materials in step (2) into deionized water, stir and completely dissolve them, dry them at 80°C for 24 hours, grind the dried mixture for 20 minutes, and then put it into a grinding tool;
[0042] (4) pressing the mixture in the mold of step (3) into a tablet using a tablet press and uniaxial hot pressing sintering, while applying ultrasonic assistance with a frequency of 30 kHz and a power of 300 W;
[0043] (5) The different uniaxial pressures in step (4) are 50 MPa, 100 MPa, 200 MPa, 300 MPa and 400 MPa, respectively. The temperature is controlled at 125 °C by an external heating coil and a temperature controller, and the sintering time is 30 min.
[0044] (6) After sintering, the power is turned off, the pressure is released, the sample is cooled, demolded and dried to obtain a ceramic sheet. The luminescence intensity of the sample is optimal when the uniaxial pressure is 300 MPa.
[0045] Embodiment 4: A rare earth doped alkali metal chloride composite ceramic and a cold sintering preparation method thereof, specifically comprising the following steps:
[0046] (1) KOH, NaOH and NH4Cl with a purity of 99.7% were added to HCl solution, concentrated and evaporated at 80°C to obtain a solid mixture, the solid mixture was placed in a quartz container and vacuum dehydrated at 250°C for 2 h, and then the product was calcined at 450°C in an inert atmosphere to obtain K with a purity of 99.9%. 0.5 Na 0.5 Cl raw material;
[0047] (2) K with a purity of 99.9% 0.5 Na 0.5 Cl and EuCl3 were weighed in a stoichiometric ratio of 1:0.008, and polyethylene glycol (PEG) accounting for 0.4% of the total weight of the raw materials was added;
[0048] (3) Add the weighed raw materials in step (2) into deionized water, stir and completely dissolve them, dry them at 80°C for 24 hours, grind the dried mixture for 20 minutes, and then put it into a grinding tool;
[0049] (4) pressing the mixture in the mold of step (3) into a tablet using a tablet press and uniaxial hot pressing sintering, while applying ultrasonic assistance with a frequency of 40 kHz and a power of 400 W;
[0050] (5) The uniaxial pressure in step (4) was 300 MPa, the temperature was controlled at 125 °C by an external heating coil and a temperature controller, and the sintering time was 30 min;
[0051] (6) After sintering, the power is turned off, the pressure is released, the ceramic sheet is obtained after cooling, demolding and drying.
[0052] The above embodiments are preferred implementations of the present invention and cannot be used to limit the protection scope of the present invention. Without departing from the spirit and essence of the present invention, any equivalent changes or equivalent modifications made by those skilled in the art to the present invention shall fall within the protection scope of the present invention.
Claims
1. A rare earth doped alkali metal chloride composite ceramic and a cold sintering preparation method thereof, characterized in that: The following steps are involved: (1) Raw material purification: KOH, NaOH and NH4Cl with a purity of 99.7% were added to HCl solution, and the mixed solution was concentrated and evaporated at 60℃~100℃ to obtain a solid mixture. The solid mixture was placed in a quartz container and vacuum dehydrated at 230℃~260℃ to obtain a dehydrated product. The product was then calcined at 420℃~480℃ in an inert atmosphere to obtain K with a purity of 99.9%. x Na 1-x Cl (0.1≤x≤0.9) raw material; (2) K with a purity of 99.9% x Na 1-x Cl and EuCl3 are weighed in stoichiometric ratio. x Na 1-x The molar ratio of Cl to EuCl3 is 0.5:(0.002 - 0.02), and an organic flux accounting for 0.1 - 1% of the total mass of the raw materials is added; (3) Add the weighed raw material in step (2) into deionized water (resistivity not less than 18 MΩ·cm), stir and completely dissolve, the mass ratio of raw material to deionized water is 1:(3 - 5), dry at 60 - 100 °C for 15 - 25 h, grind for 10 - 20 min, and then put into a grinding tool; (4) The mixture in the mold of step (3) is subjected to uniaxial hot pressing sintering, while applying ultrasonic assistance with a frequency of 20-40 kHz and a power of 100-500 W, the uniaxial pressure is 50-400 MPa, the pressure application and pressure release rate is 5-10 MPa / min, the sintering temperature is 100-225°C, the sintering time is 20-30 min, the sintering heating and cooling rate is 8-15°C / min, and after sintering, the power is turned off, the pressure is released, the ceramic sheet is cooled, and the mold is demolded and dried to obtain the ceramic sheet.
2. The rare earth doped alkali metal chloride composite ceramic and the cold sintering preparation method thereof according to claim 1, characterized in that: The organic flux is polyethylene glycol (PEG).
3. The rare earth doped alkali metal chloride composite ceramic and the cold sintering preparation method thereof according to claim 1, characterized in that: The application time of the ultrasonic wave is 50-80% of the whole sintering process.
Citation Information
Patent Citations
High pure anhydrous composite rare earth halide and preparation method thereof
CN106745163A
High purity anhydrous composite rare earth halide and preparation method thereof
CN106753378A
Preparation method of ceramic composite material and ceramic composite material, light source apparatus
CN107805056A
Low-temperature sintering method of garnet type inorganic solid electrolyte material
CN111662095A
Molybdate luminescent ceramic material for laser display as well as preparation method and application thereof
CN112500161A